Analisis Determinan Perilaku Pimpinan Industri Kecil Tahu – Tempe Dalam Mengolah Air Limbah di Wilayah Kecamatan Candisari, Kota Semarang - Sukamto, Sukamto; Widjanarko, Bagoes; Wahyuningsih, Nur Endah (Jurnal Kesehatan Lingkungan Indonesia, 2003)
ABSTRACK Background : Industrial sector has a big role in performing standard of health. The environmental quality decresed mostly happened in several places, notably in big cities, because of the bad behavior of industrial-waste banishment. The district of Candisari is one of nine districts in the City of Semarang, where 70 small industries crushed-soybeans and fermented- soybeans products exits; the most are in the city. The result of the preliminary study revealed that the waste water volume from each industry ranges from 800 liters to 1000 liters per day. Generally, these amounts of waste-water were wasted directly into the river of Kalibajak without pre treatment. Mean while, reviewing toward several member of society, who lived around the river, revealed that there were complaints of unpleasant smell and river shallowness supposed to result from the sedimentation of Industrial waste of crushed-soybeans and fermented-soybeans products. Therefore, the objective of this study was to examine the factors affected the practice of waste-water processing by the performers of small industry of crushed-soybeans products. Methods : This is an explanatory study using survey method with Cross Sectional design. The study took place in the district of Candisari, Semarang. The subjects of the study were all of the performers of small industry of crushed-soybeans and fermented-soybeans products in the district, which were 70 persons. As for crosscheck, Deep-seated interviews were carried out in triangulation manner towards 12 public figures, one health officer, and one officer of the Regional Body of Environmental Impact Control (Bapedalda), City of Semarang. The data would be analyzed using Chi-Square technique, and multivariate analysis was performed using logistic regression test. Results : The results of the logistic regression with backward stepwise method study reveals that the effect of the level of education on practice is 2.297 times, the effect of social environment on practice is more than 3.109 times. Mean while, level of knowledge, the cost consideration and attitude in this study have no effects on the practice of waste-water processing by the performers of small industry. Conclusion : The social environment is the most dominant variable on the practice of waste-water processing by the performers of small industry of crushed-soybeans and fermented-soybeans products and its effect is 3.109 times. The recommendation of this study suggest that support from public figures, the health Government Office of Semarang City (the continuous guidance toward the small industry to perform the clean and healthy environment. Key word : Determinant behavior of small industry performer, waste water management, Semarang, 2004.